2018
DOI: 10.1101/405985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutant screen for reproduction unveils depression-associated Piccolo’s control over reproductive behavior

Abstract: Successful sexual reproduction involves complex, genetically encoded interplay between animal physiology and behavior. The rat provides a highly fecund mammalian model for studying how the brain impacts reproduction. Here, we report a forward genetics screen in rats to identify genes that affect reproduction. A panel of 18 distinct rat strains harboring Sleeping Beauty gene trap mutations were analyzed for the ability to reproduce. As expected, our mutant screen identified genes where reproductive failure was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…Intriguingly, Pclo gt/gt rats display a reduced expression of the GABA A α6 subunit at MF rosettes (Figure 6). This is in line with findings from Medrano et al (2019), who performed RNA sequencing on the Pclo gt/gt rats and found a severe reduction in GABA A α6 subunit gene expression.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Intriguingly, Pclo gt/gt rats display a reduced expression of the GABA A α6 subunit at MF rosettes (Figure 6). This is in line with findings from Medrano et al (2019), who performed RNA sequencing on the Pclo gt/gt rats and found a severe reduction in GABA A α6 subunit gene expression.…”
Section: Discussionsupporting
confidence: 91%
“…In behavioral tests, we observed that Pclo gt/gt rats performed significantly worse than both Pclo wt/wt and Pclo wt/gt littermates at motor function tasks, highlighting the recessive nature of the behavioral impairments. Our colleagues Medrano et al (2019) also observed epileptic seizures and increased aggression in Pclo gt/gt rats, and a failure to reproduce due to impaired brain-gonad signaling.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations